2020
DOI: 10.1080/15332640.2020.1836703
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of hookah smoking frequency among women in the South of Iran: A cross-sectional study

Abstract: Background: The prevalence of hookah smoking (HS) has grown over the past decades in Iran especially in the south of the country. This study aimed to determine the behavioral and socio-demographic predictors of the HS frequency among women in southern Iran. Method: This research was conducted on 400 female hookah smokers selected through multi-stage sampling method. Data were collected from October 2018 to September 2019 using a questionnaire guided by literature. Ordinal logistic regression analysis was run t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…It seems that higher education has led to an increase in knowledge among women. In another study, the number of hookah users among women decreased with increasing education (23), which corroborates with the finding of the current study. Contrary to the results of the present study, another study reported that education has a preventive effect on the rate of hookah use (24).…”
Section: Discussionsupporting
confidence: 92%
“…It seems that higher education has led to an increase in knowledge among women. In another study, the number of hookah users among women decreased with increasing education (23), which corroborates with the finding of the current study. Contrary to the results of the present study, another study reported that education has a preventive effect on the rate of hookah use (24).…”
Section: Discussionsupporting
confidence: 92%
“…The study results also demonstrated that participation in social activities and belief in social values derived from social settings such as family, school, and peer groups have a protective role against the use of waterpipe, cigarettes, and alcohol (46). In Bandar Abbas, waterpipe use has a cultural root and (49). In a study in Iran, 40.6% of people mentioned that WPS is a healthier and less dangerous way to smoke tobacco (19).…”
Section: Discussionmentioning
confidence: 70%
“…According to the latest statistics from Iran, waterpipe use is about 10 times higher among males than females; this may be due to the higher rate of high-risk Prevalence of Waterpipe Smoking in Iran http://thj.hums.ac.ir http behaviors among males and the greater attention females pay to their health (52). The results of a study by Dadipoor et al revealed that about half of females experienced WPS with their friends for the first time (49). The findings of the study by Sighaldeh et al represented that having a positive attitude towards waterpipe use and its availability was an important factor in starting to use waterpipe in females (47).…”
Section: Discussionmentioning
confidence: 99%
“…The present findings showed that higher education was associated with less tobacco use. With this respect, a body of research demonstrated that low education was the main reason for a higher tendency to tobacco use (24,25). Conversely, some studies reported no effect of the education level on protection against tobacco use (14,26).…”
Section: Discussionmentioning
confidence: 99%